Exosomes as Theranostic Targets: Implications for the Clinical Prognosis of Aggressive Cancers - Gulati, Richa; Nandi, Dhruva; Sarkar, Koustav; Venkataraman, P.; Ramkumar, K. M.; Ranjan, Priya; Janardhanan, Rajiv (Frontiers in Molecular Biosciences, 2022)
Exosomes are extracellular vesicles produced by various cell types and extensively distributed in physiological fluids. Because of their significant role in cancer progression, they have been a focal point for the novel cancer therapy approach. Exosomes are highly efficient at transporting proteins, RNAs, and small drugs into cancer cells for therapeutic purposes. In addition to their prominent role as potential biomarkers for transporting targeted information from their progenitor cells, exosomes have also emerged as a new avenue for developing more effective clinical diagnostics and therapeutic techniques, also known as exosome theranostics. Lipids, proteins, and nucleic acids transported by exosomes were investigated as potential biomarkers for cancer diagnosis, prognosis, and future cancer treatment targets. The unique mechanism of exosomes and their therapeutic as well as diagnostic uses, also known as theranostic applications of exosomes in malignancies, are discussed in this review.